PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS DALAM PEMECAHAN MASALAH DI KELAS IX-6 SMPN 8 BANDA ACEH - Duskri, M.; Maidiyah, Erni; Risnawati, Risnawati; Ilham, Sri (Al-Khawarizmi, 2017)
The background of this study is the low level-achievement of students’ mathematical communication in solving problems of students grade 9 (Classroom IX-6), SMP Negeri 8 Banda Aceh. The results of the pre-test showed that 60% students only write the given information, 52% students only write the asking-problems, 4% students successfully make model/mathematical representation, 80% students write the formulas, 100% students write calculating operation, 72% students solve problems in well ordering and 64% students write summaries. The purposes of this study was to determine: (1) the way of applying Problem Based Learning (PBL) model enhancing students mathematical communication ability in solving problems, and (2) enhancing students mathematical communication in solving problems after applying PBL model. The Classroom Action Research (CAR) conducted in two cycles in 25 students. The data was collected by using teachers’ activity form and students’ activity form in teaching learning instruction of problem based learning model, test of students’ achievement in essay formed problem solving items, and rubric of students’ mathematical communication in assessing student mathematical problem solving. The observation data was analysed by describing instructional process based on the lesson plan, students’ achievement was analysed based on assessing rubric and scoring the percentage of minimal student achievement. The results showed: (1) the way of conducting problem based learning model is able to enhance students’ mathematical communication namely applying problem based learning model based on the steps of the model that have been improved to 12 steps, stress on students’ activity in each step, pose contextual problems based on real world problems, guides to applying steps of mathematical communication in each students’ worksheet (LKPD), and give real appreciation to students who ask and respond teachers’ questions and (2) students’ achievement in cycle I that achieve the minimal students’ achievement only 44%, meanwhile in cycle II increase to be 100%, on the other hand, students mathematical communication in cycle I only 60% students achieve the minimal students’ achievement increase to be 95,83% in cycle II . The Result showed that that 91,67% students only write the given information, 93,75% students only write the asking-problems, 85,42% students successfully make model/mathematical representation, 100% students write the formulas, 97,92% students write calculating operation, 85,42% students solve problems in well ordering and 97,92% students write summaries